Gambaran Pengetahuan Ibu Tentang Stimulasi Tumbuh Kembang Balita Di Wilayah Kerja Puskesmas Guntur Garut Tahun 2018 - Fatnamartiana, Senvi; Yamin, Ahmad; Purnama, Dadang (; Vol 5 No 1 (2019): jurnal kesehatan bhakti husadaDO - 10.37848/jurnal.v5i1.20, 2019)
Mother is one of children’s closest person and has important role to stimulate their growth development. Mother’s lack stimulation can result in slow growth and development of the children. This research is aimed at finding out the description of maternal knowledge about toddler growth and development in the working area of Guntur Health Center. The research design used was descriptive quantitative method. The population of this study was toddler mothers in working area of Guntur Health Center. 96 people as samples were selected by using accidental sampling technique. The research instrument used was questionnaire consisting of 31 multiple choice questions. The research result showed that most of the mothers had poor knowledge (67.7%) and good knowledge (32.2%). Then the result was divided into several categories. Regarding to growth stimulation, 52.1% of mothers had good knowledge and 47.9% with poor knowledge. In terms of development growth, 85.4% of mothers had good knowledge and 14.6% had poor knowledge. Relating to the gross motor stimulation, it was obtained 25% of mothers had good knowledge, and 14.6% had poor knowledge. In terms of fine motor stimulation, 32.3% of mothers had good knowledge and 67.7% had poor knowledge. 58.3% of mothers had good knowledge and the other 41.7% had poor knowledge relating to the knowledge of speech and language stimulation. In terms of knowledge about social and independence stimulation, 66.7% of mothers had good knowledge and 33.3% were in poor knowledge. The research concludes that the knowledge of gross and fine motor is in poor category. Overall, most of mothers are in poor knowledge; therefore, it is suggested that the health center and nurse community or village midwife improve mother’s education.